2012
DOI: 10.5539/elt.v5n4p116
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles, Personality Types and Reading Comprehension Performance

Abstract: This research aims to know whether there is a significant difference between reading and listening comprehension scores based on their learning styles; visual and auditory, of the 8th-grade students of SMPN 4 Pallangga Gowa in academic year 2016-2017. This study used quantitative method and causal-comparative design. The instruments of this study included learning style questionnaire, reading comprehension test, and listening comprehension test. Further, it used independent sample t-test to analyze the data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 32 publications
3
41
0
1
Order By: Relevance
“…Based on this conclusion, it can be suggested that learning-style based activities are more effective on reading comprehension achievement than traditional reading comprehension activities designed without considering learning styles. This result is consistent with recent studies (Al-Hajaya & Al-Khresheh, 2012;Khademi, Motallebzadeh, & Ashraf, 2013;Sadeghi, Kasim, Tan, & Abdullah, 2012) which emphasize the positive effects of instruction compatible with students' learning style preferences on their reading comprehension achievement in second/foreign language classes. Al-Hajaya and Al-Khresheh (2012) indicate that instructional strategies that are compatible with students' learning styles have a valuable role in enabling students to take control of their own learning and to maximize the potential for learning, and therefore contribute to reading comprehension.…”
Section: Discussion Of the First Hypothesissupporting
confidence: 82%
See 1 more Smart Citation
“…Based on this conclusion, it can be suggested that learning-style based activities are more effective on reading comprehension achievement than traditional reading comprehension activities designed without considering learning styles. This result is consistent with recent studies (Al-Hajaya & Al-Khresheh, 2012;Khademi, Motallebzadeh, & Ashraf, 2013;Sadeghi, Kasim, Tan, & Abdullah, 2012) which emphasize the positive effects of instruction compatible with students' learning style preferences on their reading comprehension achievement in second/foreign language classes. Al-Hajaya and Al-Khresheh (2012) indicate that instructional strategies that are compatible with students' learning styles have a valuable role in enabling students to take control of their own learning and to maximize the potential for learning, and therefore contribute to reading comprehension.…”
Section: Discussion Of the First Hypothesissupporting
confidence: 82%
“…Al-Hajaya and Al-Khresheh (2012) indicate that instructional strategies that are compatible with students' learning styles have a valuable role in enabling students to take control of their own learning and to maximize the potential for learning, and therefore contribute to reading comprehension. Sadeghi et al (2012) approaches the relationship between learning styles and reading comprehension in foreign languages in terms of personality as the basis of learning styles. They assert individual differences such as learning styles and personality traits should be taken into account in foreign language reading classes.…”
Section: Discussion Of the First Hypothesismentioning
confidence: 99%
“…More specifically, conscientiousness has been shown to be strongly related to science achievement (Eilam et al, 2009) and interest (Fesit, 2012). However, a recent review highlights inconsistencies within the research examining personality and reading comprehension and appeals for more research to examine the potential relationships between these factors (Sadeghi et al, 2012).…”
Section: The Role Of Individual Differencesmentioning
confidence: 99%
“…To Sadeghi et al (2012), reading comprehension is a process of unlocking meaning from connected text. Reading comprehension as a great source of knowledge has been one of the important parts in second/foreign language tests and examinations.…”
Section: Significance Of the Studymentioning
confidence: 99%